"Air bubble artefact": a new type of artefact on CT head examination. Issue 10 (October 2016) - McVey, S.; Kanodia, A.K.; Dundas, S.; Main, G.; Pillai, S.; Prasad, G.; Flinn, J.; Zealley, I.; Brauer, K.; Schembri, N.; Docherty, S.; Webster, A.; et al.
Highlights: Air bubble artefact is a new type of CT artefact on CT heads. It is produced by gas bubbles in the tube oil cooling system. It can cause inconsistent, illdefined areas of low attenuation mimicking pathologies. The usual physics checks and QC may be inadequate to confirm these. Equipment manufacturers may lack automatic alarms to detect these.